Ability of Medical and Nursing Healthcare Professionals from Primary Care to Identify Palliative Care Patients: Capacidade dos Profissionais de Saúde de Medicina e Enfermagem dos Cuidados de Saúde Primários em Identificar Doentes de Cuidados Paliativos - Innis, Mariana van; Capelas, Manuel Luís; Caldas, Alexandre Castro (Gazeta Médica, 2017)
INTRODUCTION: Palliative care is a specialized type of healthcare directed to individuals with chronic conditions. According to recent data, only a proportion of the Portuguese population has access to this care, the number of cases referred to specialized teams still falling below what would be expected. Doctors and nurses from primary care can play a relevant role in identifying and referring individuals, as they represent their first contact point with the Portuguese National Healthcare Service. OBJECTIVE: Assess the ability of doctors and nurses from primary care to identify palliative care patients and determine facilitating personal factors. MATERIAL & METHODS: Analytical and cross-sectional study, undertaken by submitting a questionnaire to 49 medical and nursing healthcare professionals from two Primary Care Trusts in Lisbon, Portugal, between June and September 2014. Statistical analysis of the data was conducted using the SPSS® 20. RESULTS: Only 14.3% of the sample correctly identified the clinical cases referred to palliative care. From the analyzed contributing factors, two were of statistical significance (p < 0.05) in identifying palliative care patients: personal involvement in this area and specific training. CONCLUSIONS: The results obtained demonstrate the need it is essential to strengthen palliative care training among health professionals and facilitate communication between the different elements involved in identifying and referring patients.